2005
DOI: 10.1063/1.1889090
|View full text |Cite
|
Sign up to set email alerts
|

Quasistatic magnetic and electric fields generated in intense laser plasma interaction

Abstract: A self-consistent kinetic model based on relativistic Vlasov–Maxwell equations is presented for the generation of quasistatic spontaneous fields, i.e., both the quasistatic magnetic (QSM) field and the quasistatic electric (QSE) field, in intense laser plasma interaction. For the circularly polarized laser, QSM field includes two parts, the axial part Bz as well as the azimuthal Bθ; the QSE field Es, corresponding to the space-charge potential, forms a plasma density channel. For the linearly polarized laser, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…The study of the modulation instabilities of electromagnetic waves can be significant in fast ignition scheme for ICF [11]. Recent experiments [26] and simulation studies [27,28] have confirmed that self-generated magnetic fields increase with the laser intensity, the effects observed under the present study are expected to become more significant for relativistic laser beams interacting with magnetized plasma.…”
Section: Discussionsupporting
confidence: 73%
“…The study of the modulation instabilities of electromagnetic waves can be significant in fast ignition scheme for ICF [11]. Recent experiments [26] and simulation studies [27,28] have confirmed that self-generated magnetic fields increase with the laser intensity, the effects observed under the present study are expected to become more significant for relativistic laser beams interacting with magnetized plasma.…”
Section: Discussionsupporting
confidence: 73%
“…In this case, E Sr = E Sy = ( , where B 0 is the amplitude of the magnetic field and can be obtained from the simulation results [27,28]. Then the equations of motion for the test electron can be written as dp…”
mentioning
confidence: 99%
“…5,6 Analytical modelling of the selfgenerated electromagnetic fields in the laser-plasma interaction are also useful for estimating the contribution of these fields in laser-driven particle acceleration. [10][11][12] In this paper we focus our attention on the laser-plasma interaction in the bubble regime. In particular, we study the electron cavity and the corresponding electromagnetic fields by means of an analytical model partially based on the results of PIC simulations.…”
Section: Analysis Of the Electromagnetic Fields And Electron Acceleramentioning
confidence: 99%